Transapical mitral valve implantation for treatment of symptomatic mitral valve disease: a real‐world multicentre experience. (10th February 2022) - Wild, Mirjam G.; Kreidel, Felix; Hell, Michaela M.; Praz, Fabien; Mach, Markus; Adam, Matti; Reineke, David; Ruge, Hendrik; Ludwig, Sebastian; Conradi, Lenard; Rudolph, Tanja K.; Bleiziffer, Sabine; et al.
Abstract : Aims: Transcatheter mitral valve implantation (TMVI) is a new treatment option for patients with symptomatic mitral valve (MV) disease. Real‐world data have not yet been reported. This study aimed to assess procedural and 30‐day outcomes of TMVI in a real‐world patient cohort. Method and results: All consecutive patients undergoing implantation of a transapically delivered self‐expanding valve at 26 European centres from January 2020 to April 2021 were included in this retrospective observational registry. Among 108 surgical high‐risk patients included (43% female, mean age 75 ± 7 years, mean STS‐PROM 7.2 ± 5.3%), 25% was treated for an off‐label indication (e.g. previous MV intervention or surgery, mitral stenosis, mitral annular calcification). Patients were highly symptomatic (New York Heart Association [NYHA] functional class III/IV in 86%) and mitral regurgitation (MR) was graded 3+/4+ in 95% (38% primary, 37% secondary, and 25% mixed aetiology). Technical success rate was 96%, and MR reduction to ≤1+ was achieved in all patients with successful implantation. There were two procedural deaths and 30‐day all‐cause mortality was 12%. At early clinical follow‐up, MR reduction was sustained and there were significant reductions of pulmonary pressure (systolic pulmonary artery pressure 52 vs. 42 mmHg, p < 0.001), and tricuspid regurgitation severity ( p = 0.013). Heart failure symptoms improved significantly (73% in NYHA class I/II, p < 0.001). Procedural success rate according to MVARC criteria was 80% and was not different in patients treated for an off‐label indication (74% vs. 81% for off‐ vs. on‐label, p = 0.41). Conclusion: In a real‐world patient population, TMVI has a high technical and procedural success rate with efficient and durable MR reduction and symptomatic improvement. Abstract : Procedural success at 30 days (according to MVARC), functional outcome (NYHA class) and MR severity at baseline and follow‐up. M R, mitral regurgitation; MVARC, Mitral Valve Academic Research Consortium; NYHA, New York Heart Association.